Expressing cd38 as an important prognostic factor in chronic lymphocytic leukemia - Hussain, Firas; Akel, Samer; Artin, Sujek (Latakia University Journal -Medical Sciences Series, 2019)
Background: Chronic lymphocytic leukemia is the most common type of leukemia in western countries . Cell-surface expression of CD38 in CLL has been recognised recently as a marker of progressive disease and poor outcome. Aim : The aim of this study was to evaluate CD38 expression in Syrian patients with chronic lymphocytic leukemia (CLL) and to determine its association with clinical and laboratory characteristics of the disease. Materials and Methods : This study was conducted between2012-2018 on 149 newly diagnosed CLL patients at the Hematology Unit , Internal Medicine Department , Department of Chemotherapy and Radiotherapy ,Tishreen University Hospital . All patients were subjected to full history taking, thorough clinical examination , and laboratory investigations , including detection of CD38 expression by flow cytometry suing a cutoff of 25% for positivity . CD38 expression and its associations with some other prognostic factors such as Binet stage , Rai stage , lymphocyte count in peripheral blood , hemoglobin level and serum LDH were analyzed using the Statistical Package for the Social Science, version 20 . Results : In our study group , 69 patients (46.3%) were positive for CD38 expression . Positive CD38 expression (≥25%) on peripheral lymphocytes was associated with aggressive disease of both Binet and Rai stages at the time of diagnosis (P<0.05) . Furthermore , the presence of higher serum LDH , WBC and lymphocyte count , lower platelet count and hemoglobin level were strongly correlated with CD38 positivity (P<0.05). CD38 positivity identified a subgroup of CLL patients with a more need for intensive treatment (P<0.05) . Conclusion : CD38 expression at a cutoff level of 25% seems to be a valuable prognostic factor . الخلفية : الابيضاض اللمفاوي المزمن (CLL) هو أشيع الابيضاضات لدى البالغين في البلدان الغربية. تمّ الاعتراف بأنّ التعبير عن CD38 على السطح الخلوي كواسمٍ للمرض المترقي و النتائج السيئة . الهدف : كان الهدف من هذه الدراسة هو تقييم التعبير عن CD38 عند مرضى الابيضاض اللمفاوي المزمن السوريين و تحديد ارتباطه مع الخصائص السريرية و المخبرية للمرض . المواد و الطرق : هذه الدراسة المقطعية – المستعرضة (راجعة) بين أعوام 2012 – 2018 شملت 149 مريض CLL مشخص حديثاً قبل بدء المعالجة في شعبة أمراض الدم , قسم الأمراض الباطنة , ومركز المعالجة الكيماوية والشعاعية, مشفى تشرين الجامعي . تم جمع بيانات جميع المرضى من قصة مرضية , فحص سريري, و استقصاءات مخبرية شملت كشف التعبير عن CD38 عبر إجراء flow cytometry باستخدام مستوى قطع (cutoff level) للإيجابية 25%. تمّ تحليل التعبير عن CD38 و ارتباطه مع بعض العوامل الإنذارية الأخرى مثل تصنيف Binet , تصنيف Rai , عدد اللمفاويات في الدم المحيطي , مستوى الخضاب و تركيز LDH المصلي باستخدام الحزمة الإحصائية للعلوم الاجتماعية (SPSS) النسخة 20 . النتائج : في دراستنا , امتلك 69 مريض (46.3%) تعبيراً إيجابياً عن CD38 . ترافقت إيجابية التعبير عن CD38 (≥ 25%) عند التشخيص مع مرضٍ أكثر عنفاً وفقاً لتصنيفي Binet و تصنيف Rai (P<0.05) . إضافة إلى ذلك, وجد ارتباط قوي بين المستويات المرتفعة لكل من LDH , تعداد الكريات البيض و تعداد اللمفاويات المحيطي و المستويات المنخفضة لكلّ من تعداد الصفيحات و تركيز الخضاب مع إيجابية التعبير عن CD38 (P<0.05) .حدّدت إيجابية التعبير عن CD38 مجموعةً فرعيةً من مرضى CLL الذين احتاجوا علاجاً مكثفاً (P<0.05) . الخلاصة : يبدو أنّ التعبير عن CD38 بمستوى قطع 25% هو عامل إنذاري قيّم .